HIV Infection in Sindh, Pakistan: Outbreaks, Challenges, and Recommendations - Nasreen Inayat Bughio (Journal of Liaquat University of Medical & Health Sciences, 2024)
Human Immunodeficiency Virus (HIV) infection remains a significant public health and medical problem worldwide. Today, there are over 40 million persons living with HIV (between the age of 15-49) worldwide. More than 630,000 individuals have died from AIDS-related illnesses in 2022. However, due to adherence to HIV Anti-Retroviral Therapy (ART), AIDS-related deaths have decreased by 69% in 2022.